AB0915 A Low-Penetrance NLRP3 Variant in A NOD2 Carrier Possibly Worsens The Phenotype of Blau Syndrome. (15th July 2016) - Galozzi, P.; Sfriso, P.; Basso, D.; Scanu, A.; Oliviero, F.; Plebani, M.; Punzi, L.
Abstract : Background: Blau syndrome (BS) is a rare autosomal dominant autoinflammatory syndrome that primarily affects skin, joints, and eyes, with varying severity of inflammation, and results from mutations in the NOD2 gene 1 . NOD2 bears highly conserved residues and structural similarities to the NLRP3 protein, a key component of the inflammasome which mutations underlie some autoinflammatory disorders, named cryopyrinopathies. Objectives: This study assessed the potential contribution of NLRP3 mutations to the inflammatory BS phenotype in an Italian affected family carrying p.E383K NOD2 mutation (Fig. 1 ). Methods: Genomic DNA was isolated from blood samples of the four affected family members and sequence analyses of NLRP3 were performed by an ABI 3730XL DNA sequencer (Applied Biosystems). A genotype/phenotype correlation of the carriers of NLRP3 variations was also assessed. To explain the differences in inflammatory phenotype severity, peripheral blood mononuclear cells (PBMC) were isolated from patients and healthy subjects and their ability to activate NF-κB and inflammasome pathways was measured by an array-based assay (reverse phase protein array). Results: A heterozygous genetic variant of NLRP3 was found only in the proband's sample. The p.V198M mutation was known in literature as a low-penetrance mutation associated with cryopyrinopathies in symptomatic patients (Infevers database data). The proband with combined mutations presented the worsened BS phenotype (severe chronic bilateral uveitis with glaucoma, cataracts and visual impairment), whereas the three subjects with only p.E383K variant had a much milder disease. Concerning the activation of NF-κB pathway, all BS patients have raised levels of signalling key molecules (phosphorylated NF-κB p<0.05; phosphorylated IkB-α p<0.05) compared to the controls. However, the components of inflammasome pathway presented a pattern of activation related to individual patients rather than to the whole disease. Enhanced level of cleaved caspase-1, the key component of inflammasome, was noticed only in proband PBMCs (p=0.03), potentially promoted by the additional presence of p.V198M NLRP3 mutation. Conclusions: Our data strongly suggest that severe phenotype in BS may result from co-existence with mutations in genes associated with other autoinflammatory diseases, and are consistent with recently reported findings in hereditary periodic fever syndromes 2 . The synergistic effect of dual mutations can also explain the differential activation of the inflammatory pathways and may lead to appropriate targeted drug development. References: Sfriso P, Autoimm Rev. 2012 Touitou I, J Med Genet. 2013 Disclosure of Interest: None declared